Causes And Factors of The Internet in The Life of Young People (Zien Journal of Social Sciences and Humanities, 2022)
This article clearly outlines the pros and cons of the internet, now known as the spider web. Young people have been instructed on how to use the internet properly. Nowadays, instructions are given to prevent young people from being deceived in various types of internet